(3GdEMJeGdGJ (B/s - (3JjdhdJ, SGejI , s ((3GdLRGFQ (B: s (3OGQ GdMOjK ddcJGH ddWHGYI hGdfTQ hGdJhRjY(B, s, 2016)
(3jVe gPG GdcJGH eHGOF fXQjI GdEMJeGdGJ, GdeJMhdGJ GdYThGFjI, bhGfjf GdJhRjY GdEMJeGdj ddeJMhd GdYThGFj, SdSdI JeGQjf eMdhdI ddCYeGd GdehLgI hfeGPL ddEeJMGfGJ eY GdMdhd(B.s
(3HjHdjhZQGajG(B: (3U U(B.350-351 (3GdedGMb U(B.331 s
Keywords: (3GdEMJeGdGJs; (3GdQjGVjGJs